2020
DOI: 10.3390/insects11110814
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Abundance of Potential Vectors of Rift Valley Fever Virus in the North Region of Cameroon

Abstract: Rift Valley fever (RVF) is a major viral zoonosis transmitted by mosquitoes. The virus is endemic in most parts of sub-Saharan Africa and can affect humans, livestock, and wild ungulates. Knowledge of the biology of vectors of Rift Valley fever virus (RVFV) is essential for the establishment of effective control measures of the disease. The objective of this study was to determine the species diversity and relative abundance of potential RVFV vectors in the North Region of Cameroon. Adult mosquitoes were trapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…However, a study in 2018 identified Ae . albopictus at a higher latitude near the city of Garoua at 9.3° N for the first time (Rodrigue Simonet et al, 2020 ), which is in line with global distribution predictions (Kraemer et al, 2015 ).…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, a study in 2018 identified Ae . albopictus at a higher latitude near the city of Garoua at 9.3° N for the first time (Rodrigue Simonet et al, 2020 ), which is in line with global distribution predictions (Kraemer et al, 2015 ).…”
Section: Introductionsupporting
confidence: 78%
“…albopictus to extend its range into Europe and North America (Hopperstad et al, 2021 ; Takumi et al, 2009 ). For instance, in contrast to other analysis delimitation (Tedjou et al, 2019 ), Rodrigue Simonet et al ( 2020 ) found for first time Ae . albopictus in latitudes above 6° N. Further studies and molecular analysis are needed to elucidate whether Ae .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“… Species Virus Diagnosis References Ae. aegypti DENV V, V, V, P, V [ 190 , 191 , 197 , 198 , 199 ] CHIK V, V, V, P, V, V, P + V, V, V [ 190 , 191 , 197 , 198 , 199 , 200 , 201 , 202 , 203 ] ZIKV V, V, V, V, P, V [ 149 , 190 , 191 , 197 , 198 , 199 ] YFV V, V, V, P, V, V [ 190 , 191 , 197 , 198 , 199 , 204 ] RVFV V + P, V, V, V [ ...…”
Section: Resultsmentioning
confidence: 99%
“…Potential arthropod vector identification is important to understand which mosquitoes species may maintain the virus during inter-epidemic phases. It is also important to gain a clear understanding of the community composition and abundance of such mosquito species that may act as a vector for RVFV survival and transmission [9,10]. Survival of RVFV in a specific environment greatly depends on the availability of competent vectors abundance in addition to different factors such as population density of livestock, temperature conditions and rainfall.…”
Section: Introductionmentioning
confidence: 99%